Block modeling of crustal deformation in Tierra del Fuego from GNSS velocities - Mendoza, Luciano Pedro Oscar (2015)
The Tierra del Fuego (TDF) main island is divided by a major transform boundary between the South America and Scotia tectonic plates. Using a block model, we infer slip rates, locking depths and inclinations of active faults in TDF from inversion of site velocities derived from Global Navigation Satellite System observations. We use interseismic velocities from 48 sites, obtained from field measurements spanning 20 years. Euler vectors consistent with a simple seismic cycle are estimated for each block. In addition, we introduce far-field information into the modeling by applying constraints on Euler vectors of major tectonic plates. The difference between model and observed surface deformation near the Magallanes Fagnano Fault System (MFS) is reduced by considering finite dip in the forward model. For this tectonic boundary global plate circuits models predict relative movements between 7 and 9 mm/yr, while our regional model indicates that a strike-slip rate of 5.9 ± 0.2 mm/yr is accommodated across the MFS. Our results indicate faults dipping 66+6-4° southward, locked to a depth of 11+5-5 km, which are consistent with geological models for the MFS. However, normal slip also dominates the fault perpendicular motion throughout the eastern MFS, with a maximum rate along the Fagnano Lake.